Desulfurization of natural gas condensate using polyethylene glycol and water intercalated activated γ-bauxite - Behmadi, Reza; Mokhtarian, Mahsa; Davoodi, Ali; Hosseinpour, Saman (Journal of Cleaner Production, 2022)
Three different active γ-bauxite were developed from a low-grade raw boehmite ore, as a cheap and efficient adsorbent for the desulfurization of gas condensates. The first adsorbent (RBa) was developed directly through a two-stage thermochemical activation (thermal activation process followed by an acid treatment) of the boehmite ore. The other two adsorbents (PBa and WBa) were initially intercalated with polyethylene glycol (PEG) solution or water, respectively, at the optimum temperature and pressure followed by thermochemical activation to modify the pore size and active surface area. The process parameters such as pulp density and leaching time were optimized using response surface methodology (RSM) based on central composite design (CCD). Comparing the performance of prepared adsorbents to remove sulfur-containing compounds from natural gas condensate indicated the superior sulfur removal efficiency of PBa compared to WBa and non-intercalated adsorbents. Using PBa, the sulfur content was significantly reduced from 2821 ppm to <35 ppm. Characterization of the developed adsorbents indicated that after thermal activation, the pore size of the non-intercalated adsorbent was significantly reduced, which negatively affects its desulfurization efficiency. Nevertheless, the pore diameter of PBa was maintained similar to that of raw bauxite while its surface area was approximately 12-fold larger, which confirms the successful role of PEG as a lattice expansion element, improving its desulfurization efficiency.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Average pore diameter; Bauxite adsorbent; Desulfurization; Intercalation